Effect of Different PPI Herbicides on Energy Utilization, Nutrient Content and Uptake of Soybean (Glycine max L.) - , Shani Gulaiya; , K.K Jain; , Pooja Sharma; , Sahadeva Singh; , Mansi Joshi; , Kamalkant Yadav; , Ravi Kumar; , Parikha Prakash Singh (Archives of Current Research International, 2024)
A field experiment was carried out during Kharif 2019-20 at Jawaharlal Nehru Krishi Vishwa Vidyalaya's BSP Unit, Department of Agronomy, Jabalpur (M.P.). Using a Randomized Block Design, eleven weed control treatments in all were set up with three replications. The BSP Unit, Department of Agronomy, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (M.P.) was the site of a field experiment in Kharif 2019-20. Using a Randomized Block Design, eleven weed control treatments in all were set up with three replications. The study's findings showed that Diclosulam 0.9% + Pendimethalin 35% SE at 45 + 1750 g ha-1 had the highest levels of N, P, and K. The weedy check plot had the lowest N, P, and K content. Comparing hand weeding to all other treatments, the highest uptake of N, P, and K was noted. The combination of Diclosulam 0.9% + Pendimethalin 35% SE 22.5 + 875 g ha-1 showed the highest uptake of N, P, and K. Among the several herbicidal treatments, Diclosulam 0.9% + Pendimethalin 35% SE 22.5 + 875 g ha-1 (134.80 lakh k cal ha-1) was the crop that used the most energy, followed by Diclosulam 0.9% + Pendimethalin 35% SE 45 + 1750 g ha-1 (134.20 lakh k cal ha-1). Utilizing Diclosulam 0.9% + Pendimethalin 35% SE 22.5 + 875 g ha-1, the grain's utilization of energy was measured. The weed treatments in the weedy check plot used the most energy (270.68 lakh k cal ha-1). Hand weeding plot was shown to use the least amount of energy (2.12 lakh k cal ha-1).